Self‐managed abortions in Ghana: A health policy framework analysis - Emmanuel Komla Senanu Morhe; Fred Yao Gbagbo; Renee Aku Sitsofe Morhe (Wiley, 2023)
Abstract Background Self‐managed abortions (SMAs) remain a public health challenge; and are worst in deprived settings. In this policy review, we sought to analyze the legal and policy frameworks within which SMA occurs and look at how these may help improve abortion outcomes in Ghana. Methods We searched and reviewed documents on "self‐induced" or "self‐managed" abortion in Ghana from 2015 to 2022. Databases searched included Ghana Digital Attorney, PubMed Central, Google Scholar, and Repositories of Public Universities in Ghana. The key documents reviewed included the abortion law (Act 29) of Ghana, the fourth (2021) edition of the Ghana Health Services' Comprehensive Abortion Care Standards and Protocols, and the 2017 Maternal Health Survey report. Key documents reviewed included amended Act 29, Comprehensive Abortion Care policy, and standards. We then performed policy analysis using Walt and Gilson's policy triangle framework regarding the context, practice, processes, and key players. Results After a careful review of the literature, the following key themes emerged in the framework analysis: the policy environment for SMA, the practice of SMAs, key players of SMAs, consequences of induced abortions, the abortion law, and criminal connotations of SMA. We found that SMAs remain criminalized in Ghana but the local practice persists with the use of registered and unregistered abortifacients. We also observed frequent criminal connotations of SMAs in the literature but no evidence of related prosecutions. There was limited empirical evidence on the safety and efficacy of SMAs in Ghana. Conclusion From our findings, we contend that there is an unduly high criminal connotation of SMA in Ghana. We, therefore, recommend a multilevel stakeholder engagement to decriminalize SMAs to ensure improved access to safe abortions in Ghana.